Pengembangan Mi Kering Berbahan Dasar Tepung Ubi Jalar Ungu (Ipomoea batatas L.) sebagai Pangan Fungsional Tinggi Serat - Lidwina Lidwina; Puspo Edi Giriwono; Rimbawan Rimbawan (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2018)
Indonesia is currently experiencing double nutrition problems, both malnutrition and over nutrition. Over nutrition can lead to obesity and degenerative diseases. One solution to overcome this problem is developing high-fiber food products which helps to improve gastrointentestinal function. Sweet potato flour is used as a source of fiber and a source of carbohydrate. Several formulas were designed and those with the highest content of sweet potatoes and acceptance score were further analyzed. Formula 1 has a water content of 14.08%, ash content 7.11%, fat content 0.36%, protein content 7.56%, and carbohydrate content of 71.11%. Cooking loss in F1 was 19.34%. Results of the analysis showed that total phenolic content of F1 has amounted to 27.0 mg GAE/100 g. While the result of total dietary fiber content analysis was 14.65% dw or equal to 12.58% ww. However, the highest acceptance score is in Formula 3. This formula contains moisture content of 13.51%, ash content 7.07%, fat content 0.13%, protein content 9.02%, and carbohydrate content of 70.33%. Cooking loss of this formula was 13.84%. Results of the analysis showed that total phenolic content of F3 was 15.9 mg GAE/100 g. Analysis of dietary fiber content showed 13.32% dw or equal to 11.52% ww. Based on Indonesian regulations, the fiber content of both formulas can be regarded as high fiber dry noodles as in contains no less than 6 g per 100 g.